St. Patrick's Day - Kessel, Joyce K.; Gilchrist, Cathy (Minneapolis, Minn. : Carolrhoda Books, 1982)
Presents a brief account of the life of the Roman aristocrat who became Ireland's patron saint and discusses the annual holiday that honors him.
Keywords: Patrick; Saint Patrick's Day; Saints; Saint Patrick's Day